Calcium-phosphorus interactions at a nano-structured silicate surface - Southam, Daniel; Lewis, T.; McFarlane, A.; Borrmann, T.; Johnston, J. (Elsevier, 2007)
Nano-structured calcium silicate (NCS), a highly porous material synthesized by controlledprecipitation from geothermal fluids or sodium silicate solution, was developed as filler for use inpaper manufacture. NCS has been shown to chemisorb orthophosphate from an aqueous solutionprobably obeying a Freundlich isotherm with high selectivity compared to other commonenvironmental anions. Microanalysis of the products of chemisorption indicated there wassignificant change from the porous and nano-structured morphology of pristine NCS to fibrous andcrystalline morphologies and non-porous detritus. X-ray diffraction analysis of the crystallineproducts showed it to be brushite, CaHPO4?2H2O, while the largely x-ray amorphous componentwas a mixture of calcium phosphates. A two-step mechanism was proposed for the chemisorption ofphosphate from an aqueous solution by NCS. The first step, which was highly dependent on pH, wasthought to be desorption of hydroxide ions from the NCS surface. This was kinetically favoured atlower initial pH, where the predominant form of phosphate present was H2PO4-, and led to decreasedphosphorus uptake with increasing pH. The second step was thought to be a continuingchemisorption process after stabilization of the pH-value. The formation of brushite as the primarychemisorption product was found to be consistent with the proposed mechanism.